Propuesta de un Plan de acción hacia el agroturismo sostenible y sustentable en el recinto Fátima, cantón Valencia, provincia de Los Ríos, año 2018 - Valverde Salinas, Samaria Elizabeth (2018)
The present research of work proposes an action plan towards sustainable and sustainable agrotourism in the Fátima site, Valencia canton, Los Ríos province, in which four specific objectives were proposed; as a first objective, a diagnosis was made about the current situation and the level of knowledge about tourism towards the inhabitants of the site through surveys, which determined a low percentage of economic income in the agricultural sector and knowledge about Tourism, however, a large percentage of feasibility was obtained in knowing about tourism and putting into practice the agrotourism modality, in a sustainable and sustainable manner in the social, economic and environmental aspects. As a second objective, the supply and demand was determined through a study of the target market of the canton of Buena Fe and Valencia, with the purpose of knowing the reason in which it carries out tourism, the dates in which it makes its trips, what types of agro-tourism activities they would like to perform, the services they would like to access within the premises and how much they would be willing to spend for activities and services. In addition, a FODA structural analysis was carried out, according to the observation made at the Fátima site and from the market study it was possible to determine the strengths, weaknesses, threats and opportunities presented by the Fátima site. As a third objective, an inventory of the agro-tourism resources existing at the Fatima site was generated, in which five categories of Cultural Manifestations and two of Natural Attractions were obtained, according to the MINTUR model and in the fourth objective a plan of action with five strategies in which training is encouraged for owners, participation of government authorities, the design of marketing mix strategies (Price, Product, Promotion and Advertising), and the reference budget of the investment for the concept of training, physical conditioning and infrastructure, advertising and the costs of the proposed tourist circuit. Keywords: Agrotourism, sustainable, sustainable, action plan